Fuzzy cellular model for traffic data fusion - Bartłomiej PŁACZEK (Transport Problems, 2009)
In this paper the requirements for road traffic models designed to collect complex data from vehicles detectors in a traffic control system are discussed. A cellular model is proposed that uses the theory of fuzzy sets to deal with these requirements and to enable traffic data fusion from various sources. In the introduced approach all parameters of vehicles are described by means of fuzzy numbers. Vehicles are modelled individually, thus various classes of them can be taken into consideration. The model was implemented in a simulation of traffic flow at a crossroad approach. A discharge time of vehicles queue was analysed in this experiment and compared to the results of Nagel-Schreckenberg model.